Криза документознавчої освіти: навіч зі сподіванням - Бездрабко, Валентина (Видавництво Львівської політехніки, 2020)
The article is devoted to important features of the crisis of document education in Ukraine, which has an organizational and epistemological nature, contradictions in the development of specialty 029 "Information, library and archival profession", sharpening attention to key points in understanding its content.
Keywords: освіта; криза; документознавча освіта; освітня програма; державний стандарт